Longitudinal COVID-19 profiling associates IL-1Ra and IL-10 with disease severity and RANTES with mild disease - Zhao, Y; Qin, L; Zhang, P; Peng, Y; Ogg, G; Ho, L-P; McMichael, A; Knight, JC; Dong, T (American Society for Clinical Investigation, 2020)
Background Identifying immune correlates of COVID-19 disease severity is an urgent need for clinical management, vaccine evaluation and drug development. Here we present a temporal analysis of key immune mediators, cytokine and chemokines in blood of hospitalised COVID-19 patients from serial sampling and follow up over four weeks.